The Influence of Auditor Independence, Work Experience, Work Satisfaction, and Auditor Competency Against Audit Quality - Risa Nurmala Dewi; Ichsan Maulana; Mahatir Muhadzib (Universitas Trisakti, 2017)
The purpose of this research is to determine the effect of Independency of Auditor, Job Experience, Job Satisfaction and Auditor Competency toward Audit Quality. The importance of this research includes verifying theories that have developed related to the influence of auditor independence, job experience and job satisfaction and striving to prove that increasing auditor competence can be a component that improves audit quality. The population of this research comprises auditor on Public Accounting Firm located in Jakarta. The technique of determining the sample used is convinience sampling. This research uses a multiple linear regression approach. Based on the results of testing, this research proves that independency of auditor, job experience, job satisfaction and auditor competency together have effect toward audit quality. This research also proves that partially idependency of auditor and job satisfaction have positive effect toward audit quality, whereas job experience and auditor competency have no effect toward audit quality